2012
DOI: 10.1016/j.renene.2012.05.003
|View full text |Cite
|
Sign up to set email alerts
|

Wave energy converter control by wave prediction and dynamic programming

Abstract: This article appeared in a journal published by Elsevier. The attached copy is furnished to the author for internal non-commercial research and education use, including for instruction at the authors institution and sharing with colleagues.Other uses, including reproduction and distribution, or selling or licensing copies, or posting to personal, institutional or third party websites are prohibited. b s t r a c tWe demonstrate that deterministic sea wave prediction (DSWP) combined with constrained optimal con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
103
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 162 publications
(106 citation statements)
references
References 33 publications
(43 reference statements)
3
103
0
Order By: Relevance
“…Mass-spring-damper arrangements are a key ingredient in many mechanical systems (a novel application, for instance, is in renewable wave energy [17]) and are the mechanical equivalent of a resistor-inductorcapacitor (RLC) circuit, ubiquitous in electrical systems. Figure 2.1 demonstrates two masses connected in series.…”
Section: Main Results and Examplesmentioning
confidence: 99%
“…Mass-spring-damper arrangements are a key ingredient in many mechanical systems (a novel application, for instance, is in renewable wave energy [17]) and are the mechanical equivalent of a resistor-inductorcapacitor (RLC) circuit, ubiquitous in electrical systems. Figure 2.1 demonstrates two masses connected in series.…”
Section: Main Results and Examplesmentioning
confidence: 99%
“…16 Although the body of research on controls specific to offshore WAB attenuators is small, there has been considerable research into the use of controls on other WEC types. [31][32][33][34][35][36] This research has consistently shown the potential for large increases, on the order of hundreds of percent, in absorbed power with the use of advanced controls.…”
Section: Justificationmentioning
confidence: 99%
“…Although much of the literature focusing on reactive and bang-bang controls is applied to single body point absorbers or dual body point absorbers, there is nothing fundamentally limiting application of this research to WAB attenuator devices. 32,[34][35][36] Reactive controls involve applying forces to the device in phase with the wave motion that can then be tuned for maximum energy absorption at the peak frequencies that correspond to different incoming wave spectra. Bang-bang controls include latching and clutching, and allow the control output to jump between two values, a low and a high.…”
Section: Research Pathsmentioning
confidence: 99%
“…The proposed solution relies on mathematical optimization (Bertsekas 1999, Papalambros & Wilde 2000, which aims at maximizing the extracted energy from the waves. In (Li, Weiss, Mueller, Townley, & Belmont 2012) the applicability of MPC for optimizing a single non-adaptable WEC is discussed -by non-adaptability we mean that the WEC operation is restricted to a certain wave height. In (Feng & Kerrigan 2013) optimization-based techniques were also used for control of WECs.…”
Section: Introductionmentioning
confidence: 99%